Genomes of the Orestias pupfish from the Andean Altiplano shed light on their evolutionary history and phylogenetic relationships within Cyprinodontiformes - Morales, Pamela; Gajardo, Felipe; Valdivieso, Camilo; Valladares, Moises A.; Di Genova, Alex; Orellana, Ariel; Gutierrez, Rodrigo A.; Gonzalez, Mauricio; Montecino, Martin; Maass, Alejandro; Mendez, Marco A.; Allende, Miguel L. (My University, 2024)
Background To unravel the evolutionary history of a complex group, a comprehensive reconstruction of its phylogenetic relationships is crucial. This requires meticulous taxon sampling and careful consideration of multiple characters to ensure a complete and accurate reconstruction. The phylogenetic position of the Orestias genus has been estimated partly on unavailable or incomplete information. As a consequence, it was assigned to the family Cyprindontidae, relating this Andean fish to other geographically distant genera distributed in the Mediterranean, Middle East and North and Central America. In this study, using complete genome sequencing, we aim to clarify the phylogenetic position of Orestias within the Cyprinodontiformes order. Results We sequenced the genome of three Orestias species from the Andean Altiplano. Our analysis revealed that the small genome size in this genus (similar to 0.7 Gb) was caused by a contraction in transposable element (TE) content, particularly in DNA elements and short interspersed nuclear elements (SINEs). Using predicted gene sequences, we generated a phylogenetic tree of Cyprinodontiformes using 902 orthologs extracted from all 32 available genomes as well as three outgroup species. We complemented this analysis with a phylogenetic reconstruction and time calibration considering 12 molecular markers (eight nuclear and four mitochondrial genes) and a stratified taxon sampling to consider 198 species of nearly all families and genera of this order. Overall, our results show that phylogenetic closeness is directly related to geographical distance. Importantly, we found that Orestias is not part of the Cyprinodontidae family, and that it is more closely related to the South American fish fauna, being the Fluviphylacidae the closest sister group. Conclusions The evolutionary history of the Orestias genus is linked to the South American ichthyofauna and it should no longer be considered a member of the Cyprinodontidae family. Instead, we submit that Orestias belongs to the Orestiidae family, as suggested by Freyhof et al. (2017), and that it is the sister group of the Fluviphylacidae family, distributed in the Amazonian and Orinoco basins. These two groups likely diverged during the Late Eocene concomitant with hydrogeological changes in the South American landscape.
Keywords: killifish; pupfish; cyprinodontiformes; taxon sampling; divergence times; south american altiplano; phylogenetics; phylogenomics